C2orf40 inhibits hepatocellular carcinoma through interaction with UBR5. Issue 9 (25th February 2021) - Wu, Yue; Xiang, Qin; Lv, Xiaoqin; Xiang, Xia; Feng, Zhihao; Tian, Shaorong; Tang, Jun; Xiang, Tingxiu; Gong, Jianping
Abstract: Background and Aim: Hepatocellular carcinoma (HCC) urgently needs a marker for early diagnosis and targeted treatment. C2orf40 has been identified as a tumor suppressor gene in many cancers. However, the precise role and regulatory mechanism by C2orf40 contribute to HCC remain elusive and merit exploration. Methods: Reverse‐transcription PCR, quantitative real‐time PCR, and methylation‐specific PCR were used to detect expression and methylation of C2orf40 in HCC cell lines or tissues. The effects of C2orf40 in liver cancer cells were examined via colony formation, CCK8, transwell, and flow cytometric assays. The effect of C2orf40 on tumorigenesis in vivo was determined by xenografts and immunohistochemical analysis. Western blot, indirect immunofluorescence, Co‐IP, and cycloheximide (CHX) were used to further investigate the potential mechanism of C2orf40. Results: The down‐regulation of C2orf40 in hepatocellular cancer tissue samples is often related to the degree of methylation of its promoter CpG. The recovery of C2orf40 expression in HCC cell lines can induce G0/G1 phase arrest and apoptosis and also inhibit cell migration and invasion by reversing the epithelial–mesenchymal transition (EMT) process, both in vivo and in vitro. In addition, C2orf40 can increase the expression of p21 through interaction with UBR5. Conclusions: Low expression levels of C2orf40 are related to the hypermethylation of its promoter. C2orf40 can inhibit HCC through UBR5‐dependent or p53‐independent mechanisms. C2orf40 may be a diagnostic biomarker and a potential therapeutic target in HCC.